2009
DOI: 10.1016/j.anclin.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Arousal

Abstract: Elderly patients have medical and psychological problems affecting all major organ systems. These problems may alter the pharmacokinetics and/or pharmacodynamics of medications, or expose previous neurologic deficits simply as a result of sedation. Delayed arousal, therefore, may arise from structural problems that are pre-existent or new, or metabolic or functional disorders such as convulsive or nonconvulsive seizures. Determining the cause of delayed arousal may require clinical, chemical, and structural te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…The volume of distribution, clearance rate, and plasma protein binding decreased and resulted in an increase in the free plasma concentration of drugs. 9 Furthermore, compared with young people, the concentration required to attain the similar anesthetic depth, either intravenous or inhaled anesthetics, is decreased in elderly patients. 17,18 Similar to other investigators, 6e8 we also found women wakened faster from general anesthesia than men, even in cardiac surgery, which belongs to the more complex procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of distribution, clearance rate, and plasma protein binding decreased and resulted in an increase in the free plasma concentration of drugs. 9 Furthermore, compared with young people, the concentration required to attain the similar anesthetic depth, either intravenous or inhaled anesthetics, is decreased in elderly patients. 17,18 Similar to other investigators, 6e8 we also found women wakened faster from general anesthesia than men, even in cardiac surgery, which belongs to the more complex procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Although some factors have been identified to affect ROC from general anesthesia in previous studies, 6e9 such as gender 6e8 and age, 9 few studies have ever investigated factors associated with ROC time after cardiac surgery. Previous reports have shown that patients receiving aortic valve or aortic aneurysm surgery, and with prolonged cardiopulmonary bypass (CPB) time, carry a higher risk of cerebral complications after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to awaken after a surgery performed under general anesthesia is a common reason for urgent neurologic consultation in the hospital. 1 Prolonged effects of anesthesia, particularly when combined with sedative effects of other medications (such as opiates) administered during and after surgery and in patients with liver or renal dysfunction, can explain some of these cases, as illustrated by vignette 1. However, the main role of the consulting neurologist in these instances is to exclude primary neurologic disease.…”
Section: General Anesthesiamentioning
confidence: 99%
“…Delayed emergence from general anesthesia is defined as the state that patients fail to regain consciousness and make thoughtful respond to commands or stimuli 30–60 min after general anesthesia (Ellis et al., 2017). Growing age is a critical risk factor for delayed emergence not only due to the gradual decline in hepatorenal function but also due to pharmacodynamic alterations (Anastasian, Ornstein, & Heyer, 2009). It has been demonstrated that concentrations of isoflurane and sevoflurane required to maintain the value of bispectral index (BIS) below 50 (MAC BIS50 ) decrease with the advance in age (Matsuura et al., 2009), suggesting that sensitivity of aged brain to anesthetics is remarkably increased.…”
Section: Introductionmentioning
confidence: 99%